2005
DOI: 10.1097/01.jcp.0000162805.46453.e3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CYP2D6 Activity by Bupropion

Abstract: The purpose of this study was to assess the effect of bupropion on cytochrome P450 2D6 (CYP2D6) activity. Twenty-one subjects completed this repeated-measures study in which dextromethorphan (30-mg oral dose) was administered to smokers at baseline and after 17 days of treatment with either bupropion sustained-release (150 mg twice daily) or matching placebo. Subjects quit smoking 3 days before the second dextromethorphan administration. To assess CYP2D6 activity, urinary dextromethorphan/dextrorphan metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 24 publications
4
80
1
Order By: Relevance
“…The mechanism for CYP2D6 inhibition best fit a competitive model. It has been suggested that the clinical drug-drug interaction with bupropion and CYP2D6 substrates may be the result of mechanism-based CYP2D6 inhibition by bupropion (Kotlyar et al, 2005). Our investigations showed that neither bupropion nor its metabolites were metabolism-dependent CYP2D6 inhibitors (data not shown).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The mechanism for CYP2D6 inhibition best fit a competitive model. It has been suggested that the clinical drug-drug interaction with bupropion and CYP2D6 substrates may be the result of mechanism-based CYP2D6 inhibition by bupropion (Kotlyar et al, 2005). Our investigations showed that neither bupropion nor its metabolites were metabolism-dependent CYP2D6 inhibitors (data not shown).…”
Section: Resultsmentioning
confidence: 71%
“…Clinical interactions involving bupropion and coadministered CYP2D6 substrates desipramine (Shad and Preskorn 1997;Jefferson et al, 2005), dextromethorphan (Güzey et al, 2002;Kotlyar et al, 2005), and venlafaxine (Kennedy et al, 2002) are well documented. However, CYP2D6 plays an insignificant role in bupropion clearance.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in muscle stiffness may well relate to elevation of antipsychotic drug levels through de-induction of CYP 1A2 by smoking cessation [33] or inhibition of CYP 2D6 by bupropion [34].…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders included socioeconomic status (income quintiles) at cohort entry date, prior hospitalizations for bradycardia in the year prior to the index event, number of drugs prescribed in the past year [Schneeweiss et al 2001], use of other CYP2D6-inhibiting drugs in the past 90 days, and use of negative chronotropic drugs (verapamil, diltiazem, and digoxin) in the past 90 days. Although bupropion is also a CYP2D6-inhibiting antidepressant [Kotlyar et al 2005], we included it as a covariate with other CYP2D6 inhibitors rather than as an exposure antidepressant per se because its use as an adjunct for smoking cessation may have introduced bias if patients treated with bupropion were systematically different from those prescribed other antidepressants. Finally, because sertraline exhibits some CYP2D6 inhibition, particularly at high doses [Sproule et al 1997], we conducted a sensitivity analysis by removing sertraline exposure and repeating the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%